Impact of tax aggressiveness on the profitability of publicly traded companies listed on B3 - Xavier, Milena Becker (2022)
The practice of tax aggressiveness aims to alleviate the high cost of taxes caused by the complexity of tax legislation, aims to reduce tax expenditures and maximize the organizations' performance. The present study analyzes the impact of tax aggressiveness on the profitability of publicly traded companies listed on B3 in the period from 2016 to 2020, since in the Brazilian context, evidence on the relationship between this practice and the companies’ profitability is still limited. The final study sample consisted of 204 Brazilian companies and the proxies used to measure tax aggressiveness were the total Book Tax Difference (BTD) and Effective Tax Rate (ETR). Regarding the variables of profitability, the return on investments, return for shareholders and operational activities were observed. The analysis was performed using descriptive statistics, multiple regressions (with random effects) and quantiles, and the results found did not show consensus between the proxies. While the BTD points out that the greater the tax aggressiveness, the greater the profitability, the ETR shows an inverse relationship. As tax aggressiveness proxies do not show consensus in the results, it was not possible to state that higher levels of tax aggressiveness increase the profitability of publicly traded companies listed on B3. Thus, the empirical evidence allows reflections on the use of tax aggressiveness in Brazil and the managers’ decision-making.